2015
DOI: 10.20344/amp.6248
|View full text |Cite
|
Sign up to set email alerts
|

Valores de Referência da Tomografia de Coerência Óptica na Idade Pediátrica

Abstract: RESUMOIntrodução: A tomografia de coerência óptica é um exame que permite obter imagens de alta resolução dos tecidos in vivo, possibilitando a medição das estruturas oculares, nomeadamente a camada de fibras nervosas da retina e a espessura macular. Como método não invasivo torna-se particularmente útil em crianças, contudo a sua aplicabilidade está limitada pela existência de valores normativos apenas para adultos.Objetivo: Estabelecer na idade pediátrica valores normativos para a espessura da camada de fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Our study did not find statistically significant differences between male and female RNFL thickness, in accordance with an important number of studies regardless of the technology that was used [ 17 , 18 , 21 , 24 , 25 , 30 , 33 , 34 , 38 , 39 , 40 , 41 , 42 , 43 ]. Turk et al found a significant difference between female and male children in terms of RNFL only in the temporal inferior segment, without any significant difference in the other RNFL parameters [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study did not find statistically significant differences between male and female RNFL thickness, in accordance with an important number of studies regardless of the technology that was used [ 17 , 18 , 21 , 24 , 25 , 30 , 33 , 34 , 38 , 39 , 40 , 41 , 42 , 43 ]. Turk et al found a significant difference between female and male children in terms of RNFL only in the temporal inferior segment, without any significant difference in the other RNFL parameters [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Nowadays, the OCT is an indispensable tool for diagnosis and follow-up of optical neuropathies and glaucoma in adults. Many studies demonstrate its feasibility and reproducibility for pediatric age and an increase in diagnostic accuracy if the examiner had normative data for the device that is used [ 17 , 18 , 19 , 20 , 21 ]. SD-OCT is a fast, easy, and noninvasive examination that allows the clinician to quantitatively measure the thickness of the retinal nerve fiber layer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations